Maresins as novel anti-inflammatory actors and putative therapeutic targets in sepsis - Yan Sun; Shujun Sun; Pu Chen; Yan Dai; Dong Yang; Yun Lin; Lisha Yi (Elsevier, 2024)
Sepsis, a complex clinical syndrome characterized by an exaggerated host response to infection, often necessitates hospitalization and intensive care unit admission. Delayed or inaccurate diagnosis of sepsis, coupled with suboptimal treatment strategies, can result in unfavorable outcomes, including mortality. Maresins, a newly discovered family of lipid mediators synthesized from docosahexaenoic acid by macrophages, have emerged as key players in promoting inflammation resolution and the termination of inflammatory processes. Extensive evidence has unequivocally demonstrated the beneficial effects of maresins in modulating the inflammatory response associated with sepsis; however, their bioactivity and functions exhibit remarkable diversity and complexity. This article presents a comprehensive review of recent research on the role of maresins in sepsis, aiming to enhance our understanding of their effectiveness and elucidate the specific mechanisms underlying their actions in sepsis treatment. Furthermore, emerging insights into the management of patients with sepsis are also highlighted.